DEEP STRUCTURE OF THE ALTAI MOUNTAINS AND MODERN GRAVITY FIELD MODELS - V. Yu. Timofeev; D. G. Ardyukov; D. N. Goldobin; A. V. Timofeev; D. A. Nosov; I. S. Sizikov; E. N. Kalish; Yu. F. Stus (Геодинамика и тектонофизика, 2023)
The results of the ground-based absolute gravity and space geodetic measurements for the Altai Mountains were considered in combination with EIGEN-6C4 Global Geopotential Model (ETOPO1 Global Relief Model) generated from the satellite data. Analysis was made on different kinds of data: model values for the vertical component of gravity, values of Bouguer and Faye gravity reductions, variations of the vertical gravity gradient, and changes in altitude of the measurement sites. With EIGEN-6C4 model for Bouguer reduction, the crustal thickness curve was drawn along the Novosibirsk (southern West Siberia) – Ukok Plateau (Altai Mountains) line with a length of 800 km. The Moho depth increases from 40 km in the northwest of the area to 51 km in the southeast. For the homogeneous crust model, there was obtained the Moho depth distribution in the Altai Mountains and their foothills.The analysis of the results of modeling Bouguer and Faye reductions, the data on quasigeoid heights and the relationship between relief height and Bouguer anomalies implies that the Altai Mountains area as a whole is isostatically compensated. Non-compensated are some intermountain basins, such as, for example, the Kurai and Chuya valleys.